Egyes formatervezési mintaoltalmi alapfogalmak a joggyakorlat alapján - Bezzegh, Tibor (Debreceni Jogi Műhely, 2008)
The Committee of the European Union after the issue of the Directive 98/71/EC found that the integrity of the internal market needs an easily accessible uniform protection of designs that covers the whole territory of the Community. For this reason was issued the 6/2002 EC regulation on Community Designs. The most important definitions and the grounds for invalidity are absolutely identical in the directive and the regulation. May aim by this short essay is to interpret the main definitions of design law by analysing some published cases of the Office for Harmonisation in the Internal Market (OHIM). The case law has important role in the field of design law since the requirements of protection and the grounds of invalidity contain a number of unique terms can be construed only by practice. As a consequence of the harmonised design law the practice of the Office can exercise a strong guiding effect not only on the application of community design law but national level design laws in the procedure of the national offices and courts. . 25 (1) point b) is the most used ground for invalidity in practice when a conflict with Art. 4-9. occurs. Within this point lack of novelty, individual character and prior disclosure shall be mentioned first of all. In the relation of novelty and individual character it seems of the cases that lack of novelty always excludes any further examination of individual character since individuality can be considered a narrower definition of novelty. By analyzing the overall impression produced by a design to an informed user the Office always underline that the difference must be instantly and obviously recognizable. The impression shouldn’t be based on through examination of the informed user. The invalidity division stated that any prior design in important databases on internet shall be deemed to be known by the specialised circles and can result the disclosure according to the regulation. In connection with features dictated solely by its technical function the Office stated that designs contain only elements of merely technical purpose (in this case an engine block and engine parts) specific position of such elements and the general impression of the whole enough to provide legal protection for such features. There is no ground for invalidity pursuant to this reason if the same technical function can be achieved by different design. In my essay I focused on the most the above mentioned most relevant parts of some definitions. My future plan is to analyse the differences between the legal practice of different European countries concerning this issue.